George vs. George : the American Revolution as seen from both sides - Schanzer, Rosalyn (Washington, D.C. : National Geographic, 2004)
Explores how the characters and lives of King George III of England and George Washington affected the progress and outcome of the American Revolution.
Includes bibliographical references (p. 58-59) and index.
School Library Journal starred
Notable/Best Books (A.L.A.)
Library Media Connection starred
6.2
3-6
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; George -- III, -- King of Great Britain, -- 1738-1820 -- Juvenile literature; Presidents -- United States -- Juvenile literature; Generals -- United States -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Juvenile literature; Great Britain -- Kings and rulers -- Juvenile literature; United States -- History -- Colonial period, ca. 1600-1775 -- Juvenile literature; Great Britain -- History -- George III, 1760-1820 -- Juvenile literature; Washington, George, -- 1732-1799.; George -- III, -- King of Great Britain, -- 1738-1820.; Presidents; Generals; Kings, queens, rulers, etc; United States -- History -- Revolution, 1775-1783.; Great Britain -- History -- George III, 1760-1820.; Washington, George, -- 1732-1799.; George -- III, -- King of Great Britain, -- 1738-1820.; Presidents -- United States; Generals -- United States; Great Britain -- Kings and rulers; United States -- History -- 1775-1783, Revolution; Great Britain -- History -- 1714-1837.